External Factors’ Influence on Course of the April 25, 1974 Revolution in Portugal - D. N. Ermolovich (Научный диалог)
The article examines the Portuguese Revolution of 1974 from 1974 to 1976, focusing on the influence of external forces. The analysis extensively utilizes documentary materials published by the U.S. State Department during the period under consideration, as well as memoirs by Portuguese and foreign authors. The study explores the process of shaping the United States' new foreign policy towards Portugal after the revolution, comparing American and European approaches to the events in Portugal. The role of the USSR and other socialist countries is also examined. The research findings indicate that the revolution caught the American leadership off guard. Initially, the U.S. response was restrained, but their attitude changed after members of the Communist Party joined the government. The U.S. adopted a policy of exerting political and economic pressure on the Portuguese leadership to exclude communists from the government, supporting all opposition left-wing parties, and exploiting divisions within left-wing forces. The Soviet Union provided relatively modest support to Portuguese communists, while socialist bloc countries showed significantly greater involvement and enthusiasm. U.S. allies in Europe took more moderate positions. European diplomacy made significant efforts to avoid direct confrontation between the U.S. and the USSR, with the greatest challenge being to prevent the U.S. from demonstrating its power on the European continent.